Are Physiotherapists Comfortable With Person-centred Practice? An Autoethnographical Insight - Mudge, S; Stretton, Caroline; Kayes, NM (Informa Plc., 2013)
Purpose: This study aimed to understand our shared conflicting response and discomfort to person-centred rehabilitation within the context of our physiotherapy rehabilitation culture by reflecting on our own experiences as research physiotherapists and clinicians. Method: This study used autoethnographical methods to explore the personal and professional experiences of two physiotherapists in neurological rehabilitation. Data were collected through ten written reflections and five joint discussions. The data were analysed collaboratively through focused conversations and writing. We looked for patterns in our data and the literature to triangulate our findings. Joint narratives were structured based on three headings: Where we have come from, Challenges to our position and Where we are now. Results: The four main topics of discussion were goal setting, hope, the physiotherapy paradigm and person-centred practice. Physiotherapy practice is typically underpinned by a biomechanical discourse, which separates the mind and the body. This paradigm limits our ability to manage aspects of person-centred practice, such as valuing patient preferences, fostering hope, managing expectation and building a positive therapeutic relationship. Conclusion: Awareness of existing influences on theory and practice is necessary to move the physiotherapy profession towards a greater degree of understanding and application of the principles of person-centred practice.
Keywords: Physiotherapy; Person-centred practice; Critical reflection; Professional practice; Goals; Hope